Nutrient Contents and Nut Properties of Pistachio (Pistacia vera L.) Varieties - KAZANKAYA, AHMET; TUFENKCI, S.; FIKRET BALTA, M.; KARADAG, S. (Asian Journal of Chemistry, 2010)
In this study, 11 varieties (Siirt, Kirmizi, Uzun, Sultani, Ketengömlek, Halebi, Ohadi, Kerman, Kaleh Ghochi, Ahmetaga and Ekberi) and 6 promising genotypes of pistachio (Pistacia vera L.) were evaluated with respect to fruit and leaf nutrient contents (N, P, K, Ca, Mg, Fe, Mn, Zn and Cu) and some pomological characteristics. Pistachio fruits had a range of 3.44 % (A-13) - 4.21 % (A-8) in N, 1555 ppm (A- 15) - 4965 ppm (A-13) in P, 0.301 % (Halebi) -1.244 % (Ohadi) in K, 0.027 % (Kerman) - 0.754 % (Ohadi) in Ca, 0.76 % (KetengömLek) - 2.04 % (A-13) in Mg, 8.46 ppm (A-15) - 405.6 ppm (Sultani) in Fe, 1.25 ppm (Sultani) - 13.15 ppm (A-8) in Mn, 5.28 ppm (Kerman) - 43.57 ppm (A-19) in Zn and 1.90 ppm (Kerman) -17.30 ppm (A-19) in Cu. Their leaf nutrients were 1.40 %(Ohadi) - 2.18 % (Kerman) for N, 346 ppm (Kerman) - 1443 ppm (A-3) for P, 0.115 % (A-3) - 1.674 % (Siirt) for K, 3.83 % (Halebi) - 8.37 % (A-15) for Ca, 2.95 % (A-8) - 4.48 % (A-19) for Mg, 53.4 ppm (A-15) - 335.6 ppm (Kerman) for Fe, 9.2 ppm (A-19) - 52.6 ppm (A-3) for Mn, 13.5 ppm (Kerman) - 22.8 ppm (A-13) for Zn and 10.94 ppm (P-65) - 87.22 ppm (A-3) for Cu. Besides, as nut characteristics of pistachios, nut weight, kernel weight, kernel percentage and leaf stalk length were between 0.84-1.53 g, 0.50-0.82 g, 42-70 %, 3.72-6.50 cm, respectively.